The association between sociodemographic characteristics and breakfast consumption pattern among undergraduate students of Universiti Sains Malaysia, Health Campus, Kubang Kerian, Kelantan - Noor, Anis Nabila Md (Universiti Sains Malaysia, 2024)
This study identified the association between socio-demographic characteristics and breakfast consumption patterns among undergraduate students at the Health Campus of Universiti Sains Malaysia in Kubang Kerian, Kelantan. The main objective is to determine the association between sociodemographic characteristics and breakfast consumption patterns among students. A cross-sectional study was carried out among undergraduate students in, utilizing a questionnaire distributed to a sample of undergraduate students. The respondents were recruited through convenience sampling and 116 responses were included in the analysis, utilizing a structured questionnaire in collecting data. Among the 116 respondents, a majority were female (94%) and Malay (75%), with ages ranging from 19 to 28 years. Most participants were in their first, second and third year of study, and 97.4% lived in hostels. In term of breakfast consumption patterns, the study found that a considerable proportion (55.2%) consumed breakfast fewer than three times a week, with the preferred timing between 8:00 and 10:00 AM. Additionally, 75% of students spent between RM2 and RM5 on breakfast, and 65.5% preferred consuming it at home or in their hostel. The study findings indicate no significant association between several sociodemographic parameters, such as age, daily food budget, and sponsorship during studies, with breakfast consumption patterns among university students. However, other parameters show significant associations with breakfast consumption patterns. Among them, a statistically significant association was found between ethnicity and the frequency of breakfast consumption per week (p value=0.001). Lastly, it is important to promote healthy breakfast habits among university students, considering socio-demographic factors.